Clinical observation of early prenatal diagnosis of the coronary of hypospadias - S. A. Tyo; O. S. Turkina (Медицинский вестник Юга России, 2023)
Hypospadias is one of the most common congenital malformations of the male external genitalia and urethra, the main manifestation of which is meatus dystopia. There is a steady increase in the frequency of its occurrence in many countries of the world. Hypospadias have various forms of severity, which significantly affects the patient's management tactics, the volume of surgical treatment and the further prognosis for the boy's life. The article describes a case of early prenatal diagnosis of the coronary form of hypospadias in the fetus at 15 weeks of gestation, followed by postnatal verification of the diagnosis. The possibilities of echography in the early detection of distal forms of hypospadias using an integrated approach in the assessment of external genitalia in a male fetus are shown. This complex of hypospadias markers includes an assessment of the size of the penis, the presence of a curvature of its body, the shape of the head of the penis and the presence of signs of cleavage of the foreskin, which are manifested by its rounding. The ineffectiveness of the long-used «tulip» sign for the early diagnosis of distal forms of hypospadias has been demonstrated. The comparison of the echographic picture of the structure of the genitals in normal and hypospadias at 12 and 15 weeks of pregnancy was carried out.